Technology-enhanced task-based language teaching toward their self-directed language learning: ESP learners views - Mulyadi, Dodi; Singh, Charanjit Kaur Swaran; Setiawan, Anjar; Prasetyanti, Dian Candra (Universitas Syiah Kuala, 2023)
Utilising technologies to enable language learners to accept authentic and communicative assignments is proliferating, but its effect on their self-directed language learning (SDLL) needs to be investigated. To this end, the present study aimed to investigate English for specific purpose (ESP) learners views on using technology-enhanced task-based language teaching (TBLT) toward their self-directed language learning. A mixed-method approach with a sequential explanatory design with 103 nursing students as research participants. This study used two research instruments: the Likert scale and an open-ended questionnaire. Descriptive statistics, Path analysis, and thematic analysis were employed to analyse the data. The findings from quantitative data revealed that students learning needs and utilising skills of SDLL categories have a strong influence on English mastery after receiving technology-enhanced TBLT. Consequently, ESP students must also improve process planning and use skills. They should be encouraged to schedule more consistent English lessons in and out of class. Meanwhile, the qualitative data disclose that technology-enhanced TBLT assists the learners in improving their language learning, i.e., planning process, completing tasks, and internal attributions. ESP students expressed their concerns and reported some challenges in applying language skills during speaking activities. This study implies that ESP lecturers can adopt various ways to assist ESP students in mastering English language goals through technology-enhanced TBLT.